2015
DOI: 10.1007/s00214-015-1698-3
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition reaction rate of BCl3–CH4–H2 in the gas phase

Abstract: temperature. The concentration, consistent with the thermodynamics computations, of the reactants achieves a constant of consuming completely with the extension of time. The concentrations of precuts BC and C also increase with increasing temperature, and the concentration of B is always larger than BC in the temperature range of 1200-1600 K. Thus, the rich boron product is easy to form and to deposit at higher temperatures. However, the difference in concentrations (logarithm values) between BC and B becomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…Based on the most favorable reaction path previously proposed, Liu et al [28] studied the reaction rate of the BCl /CH 4 /H 2 gas-phase system. Their rate constants were calculated for temperatures within 200-2000 K and adopted G45-G58 [29]. Reinisch et al [30] reported a set of theoretical experiments of the gas-phase decomposition of boron trichloride in the presence of hydrogen radicals, and their reactions are also included (G59-G62 in Table 3).…”
Section: Model Simulation and Prediction 2 1 Reactor-scale Modelmentioning
confidence: 99%
“…Based on the most favorable reaction path previously proposed, Liu et al [28] studied the reaction rate of the BCl /CH 4 /H 2 gas-phase system. Their rate constants were calculated for temperatures within 200-2000 K and adopted G45-G58 [29]. Reinisch et al [30] reported a set of theoretical experiments of the gas-phase decomposition of boron trichloride in the presence of hydrogen radicals, and their reactions are also included (G59-G62 in Table 3).…”
Section: Model Simulation and Prediction 2 1 Reactor-scale Modelmentioning
confidence: 99%
“…Based on the most favorable reaction path previously proposed, Su et al studied the reaction rate of the BCl 3 /CH 4 /H 2 gas-phase system [25]. Their rate constants were calculated for temperatures within 200-2000 K and adopted here (G45-G58) [26]. Reinisch et al…”
Section: Reactor-scale Model (Rm)mentioning
confidence: 99%
“…14 Besides, they also demonstrate that the BCl 3 +H→BHCl 2 +Cl addition-elimination path consumes BCl 3 much faster than the direct abstraction route (BCl 3 +H→BCl 2 +HCl) proposed by Harris et al 15 In a similar study, it has been observed that the boron carbide and carbon content in the film increases with increasing temperature in the range of 1200-1600 K, and the fraction of boron is always more significant than B 4 C. Thus, the boron-rich film is easily formed at elevated temperatures. 16 In general, the manual development of a detailed mechanism is tedious and time consuming, missing out on a few reactions. However, the automatic mechanism generator (computer code) can build a large model.…”
Section: Introductionmentioning
confidence: 99%